Determination of phosphate in seawater by ion chromatography inductively coupled plasma sector field mass spectrometry. (9th August 2021) - Cheong, Chikako; Miura, Tsutomu; Nonose, Naoko
Abstract: Phosphate in three seawater certified reference materials developed in previous work (NMIJ CRM 7601‐a, 7602‐a, and 7603‐a) was not certified because it was only determined by continuous flow analysis (CFA). To obtain certified values for phosphate, we developed a novel method for the analysis of phosphate in seawater via inductively coupled plasma sector field mass spectrometry (ICP‐SFMS) combined with anion exchange ion chromatography (IC). With use of a Jet‐sampler cone and an X‐skimmer cone on the ICP‐SFMS instrument, the 31 P sensitivity derived from phosphate was enhanced by a factor of 18 compared to that of standard cones. To reduce the severe saline‐generated matrix effect, an IC with a switching‐valve system that separates phosphate from saline was employed. By adding an internal standard element (As) to the seawater samples, time‐dependent fluctuation of the 31 P sensitivity was corrected and a better calibration curve was obtained. The developed method was applied to the analysis of three types of seawater. Although NMIJ CRM 7601‐a could not be determined because its concentration after dilution for the IC separation is lower than the detection limit (0.005 μ mol kg −1 ), the analytical results for NMIJ CRM 7602‐a and 7603‐a are in good agreement with the values obtained via CFA, considering their expanded uncertainties with the coverage factor of 2. The developed method was validated by analyzing an existing certified reference material (MOOS‐3). This method enabled the measurement of sub‐ μ mol kg −1 levels of phosphate with high accuracy and sensitivity.